Relationship Between Fear of Monkeypox and Intention to be Vaccinated Against Monkeypox in a Peruvian Sample. The Mediating Role of Conspiracy Beliefs About Monkeypox - Caycho-Rodríguez, Tomás (2023)
The present study evaluated the predictive capacity of fear of Monkeypox (MPX) on the intention to be vaccinated against MPX and the influence of conspiracy beliefs as a mediating variable in this relationship in 516 Peruvian sample with an average age of 27.10 years participated. Monkeypox Fear Scale, MPX Conspiracy Beliefs Scale and a single item of intention to be vaccinated against MPX were used. Statistical analyses have included estimation of descriptive statistics for all variables in the model tested and Structural Equation Modeling to predict intention to be vaccinated against monkeypox. It has been found that fear has a positive impact on conspiracy beliefs about MPX and intention to be vaccinated against MPX. Finally, conspiracy beliefs are negatively related to intention to be vaccinated. As for indirect effects, both are statistically significant. The model explains 11.4% of the variance in beliefs and 19.1% in intention to be vaccinated. It is concluded that fear of MPX played an important role, both directly and indirectly, in the intention to be vaccinated against MPX, having conspiratorial beliefs about MPX as a mediating variable. The results have important implications for public health practices aimed at combating doubts about MPX vaccination.